OPTIMIZING THE IMPLEMENTATION OF NURSING ROUND AND NURSING HANDOVER IN FATMAWATI HOSPITAL JAKARTA: DOI: https://doi.org/10.35654/ijnhs.v2i1.65 - Nani Asna Dewi (International Journal of Nursing and Health Services (IJNHS), 2019)
Nursing is an integral part of medical services in a hospital, and its mission is to provide the continuum of care based services throughout the life cycle. Nursing round and nursing handover are substantial elements in providing nursing services and ensure patients’ safety. Optimizing the implementation of the nursing round and nursing handover aims to refresh, renew, and optimize required instruments. Therefore, renewing nurses’ knowledge and commitment is required to adopt a better change as mentioned in the hospital’s vision and mission, i.e. continuum of care. This research employed an analysis study with Fishbone analysis. The results reveal that the nurses’ knowledge of nursing round management increases by 49.25%, and their experience of conducting nursing round increases by 39.13%. It indicates a fine enhancement and proves that the implementation of nursing round and handover is effective to enhance the nurses’ knowledge of nursing round management because, in this round, nursing handover is directed and monitored. The commitment of top management plays a significant role in optimizing this program. Therefore, the current issue of patient centre care is well accommodated. Keywords: Optimization, service management, care management, handover, round